The preventive effect of mussel oil on gestational diabetes mellitus in pregnant mice fed by a high-fat and high-sucrose diet. Issue 2 (5th January 2023) - Li, Kelei; Li, Huiying; Song, Xiaolei; Kuang, Xiaotong; Liu, Shiyi; Zhu, Suqing; Li, Duo
Abstract : Mussel oil improved glucose intolerance and insulin resistance during pregnancy by modulating sphingolipds metabolism and activating insulin signaling pathway. Abstract : The present study aimed to investigate the preventive effect of mussel oil (MO) on gestational diabetes mellitus (GDM) in mice fed by a high-fat and high-sucrose (HFHS) diet. Pregnant mice were allocated to four groups: normal diet + corn oil (CO), HFHS + CO, HFHS + fish oil (FO), and HFHS + MO. The total n-3 polyunsaturated fatty acids (PUFAs) in MO (51.30%) and FO (48.25%) were comparable (mainly C22:6n-3 and C20:5n-3). HFHS + MO and HHFS + FO had a significantly lower area under the curve (AUC) for the oral glucose tolerance test (OGTT) than the HFHS + CO group. The HFHS + MO group but not HFHS + FO group had a significantly lower AUC for the insulin tolerance test (ITT) than the HFHS + CO group. The HFHS + MO group had significantly lower homeostasis model assessment-insulin resistance (HOMA-IR) and fasting serum insulin than the HHFS + FO and HFHS + CO groups. Liver sphingosine kinase 1 (SphK1) was significantly higher, while SphK2, Akt, and P-Akt were significantly lower in the HFHS + CO group compared with the normal diet + CO group. The HFHS + MO group but not the HFHS + FO group had significantly higher SphK2, Akt, and P-Akt than the HFHS + CO group. SphK2 had a strong negative correlation with the AUC for the OGTT ( r = −0.759, p = 0.001) and insulin tolerance test (ITT) ( r = −0.637; p = 0.008), fasting serum insulin ( r = −0.594, p = 0.015), fasting blood glucose ( r = −0.587, p = 0.017) and HOMA-IR ( r = −0.629, p = 0.009) and a strong positive correlation with Akt ( r = 0.594, p = 0.015) and P-Akt ( r = 0.676, p = 0.004). In conclusion, mussel oil improved glucose intolerance and insulin resistance during mice pregnancy, which was superior to the effects of fish oil.